2022
DOI: 10.1002/jeq2.20434
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus removal in a bioretention cell experiment receiving agricultural runoff from a dairy farm production area during third and fourth years of operation

Abstract: This study assessed the performance of three bioretention cells during the third and fourth years post establishment with respect to their ability to capture nitrogen (N) and phosphorus (P) in runoff from a dairy farm production area. The effects of two treatments across the three cells were evaluated: a vegetation treatment using switchgrass (Panicum virgatum L.) and a soil amendment treatment using low‐P compost (derived from leaf litter). Cell 1 has neither vegetation nor compost; Cell 2 includes vegetation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…Prior research is conflicted about the effect of embedded vegetation on nutrient and FIB removal in bioretention systems [33][34][35][36]. Chandrasena et al [37] found that vegetation had a net negative effect on E. coli survival in biofilters.…”
Section: Formentioning
confidence: 99%
“…Prior research is conflicted about the effect of embedded vegetation on nutrient and FIB removal in bioretention systems [33][34][35][36]. Chandrasena et al [37] found that vegetation had a net negative effect on E. coli survival in biofilters.…”
Section: Formentioning
confidence: 99%
“…Among other crucial considerations, the utilization of herbaceous ground coverings of at least three to four different species to stop soil layers and mulch from eroding in BRs is suggested [117]. Because of restricted water resources, deeper rooting is needed, and mixtures with a preponderance of shrubby species might be more appropriate.…”
Section: Linkage Between Vegetation Morphology and Adaptability To Fl...mentioning
confidence: 99%
“…Because of restricted water resources, deeper rooting is needed, and mixtures with a preponderance of shrubby species might be more appropriate. Plants determined for erosion control in the manual for bioretention [117] are Panicum virgatum L. (fam. Poaceae), Andropogon gerardii Vitman (fam.…”
Section: Linkage Between Vegetation Morphology and Adaptability To Fl...mentioning
confidence: 99%
See 1 more Smart Citation